Phase Transition and Electronic Structures of All-d-Metal Heusler-Type X2MnTi Compounds (X = Pd, Pt, Ag, Au, Cu, and Ni) - Wu, Mengxin; Zhou, Feng; Khenata, Rabah; Kuang, Minquan; Wang, Xiaotian (Frontiers in Chemistry, 2020)
In this work, we investigated the phase transition and electronic structures of some newly designed all-d-metal Heusler compounds, X2MnTi (X = Pd, Pt, Ag, Au, Cu and Ni), by means of the first principles. The competition between the XA and L21 structures of these materials was studied, and we found that X2MnTi favors to feature L21 type structure, which is consistent with the well-known site-preference-rule (SPR). Under L21 structure, we have studied the most stable magnetic state of these materials, and we found that the FM state is the most stable due to its lower energy. Through tetragonal deformation, we found that the L21 structure is no longer the most stable structure, and a more stable tetragonal L10 structure appeared. That is, under the tetragonal strain, the material enjoys a tetragonal phase transformation (i.e., from cubic L21 to tetragonal L10 structure). This mechanism of L21-L10 structure transition is discussed in detail based on the calculated density of states. Moreover, we found that the energy difference between the most stable phases of L10 and L21, defined as ΔEM (ΔEM = ECubic-ETetragonal), can be adjusted by the uniform strain. Finally, the phonon spectra of all tetragonal phases X2MnTi (X = Pd, Pt, Ag, Au, Cu and Ni) are exhibited, which provides a powerful evidence for the stability of the tetragonal L10 state. We hope that our research can provide a theoretical guidance for future experimentally investigations.